KRAIT BITE MANAGEMENT IN EMERGENCY DEPARTMENT AND PATIENTS OUTCOME: A SYSTEMATIC REVIEW - Singh, Rajiv Ratan; Prakash, Chandra; Kumar, Santosh; Yadav, Pradeep Kumar; Tripathi, Sachin Kumar; Yadav, Shobhna (Journal of Forensic Medicine and Toxicology, 2025)
The bite of the Krait (Bungarus species) is a vital medical emergency and requires immediate admission in emergency department for management of envenomation. [...] Timely antivenom administration and improved emergency protocols are crucial for survival.
Keywords: Antivenins; Emergency Medical Services; Krait Venoms; Neuromuscular Diseases; Snake Bites; Treatment Outcome